Gross morphology, radiology and computed tomography of the ear of the southern white rhinoceros (Ceratotherium simum simum) - Steenkamp, Gerhardus (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2020.